ANALISIS BALANCED SCORECARD MEMPENGARUHI KINERJA PDAM KOTA PALANGKA RAYA - Sri Hartini (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2020)
To the face the increase of the current business environment into a more complex situation, a method of performance measurement that can accurately and comprehensively assess the company's performance is essentially needed. In this case the method which can be used is the Balanced Scorecard. The objective of the Balanced Scorecard method is to measure the performance of the company from four perspectives, namely: learning and growth perspective, internal business process perspective, customer perspective and financial perspective.The researcher conducted the research on PDAM Palangka Raya District using the data from 2017-2019 to analyze the financial perspective, while for other perspectives using company data and calculation of questionnaires distributed to employees of PDAM Palangka Raya District.The results of the research reveals that the overall performance of PDAM Palangka Raya District is good enough, it is indicated by the value generated from the respective scorecards of each perspective. The conclusion that can be derived through the analysis is that the Balanced Scorecard is the best method in assessing the performance of the company, since the Balanced Scorecard raises the important aspects that are ignored by the traditional performance measurement, such as aspects of human resources, systems used in a corporation, operational processes, and aspects of customer satisfaction, so that the measurement results of the Balanced Scorecard is more accurate. Accurate performance measurement is very important for management, both in the process of planning, decision making, and controlling, and in realizing the vision and mission of the corporation.